Doubling the Mechanical Properties of Spider Silk by C60 Supersonic Molecular Beam Epitaxy - Pantano, Maria F.; Tatti, Roberta; Aversa, Lucrezia; Verucchi, Roberto; Pugno, Nicola M. (Frontiers in Materials, 2020)
Spider silk is one of the most fascinating natural materials, owing to its outstanding mechanical properties. In fact, it is able to combine usually self-excluding properties, like strength and toughness that synthetic fibers fail to replicate. Here, we report a method to further enhance the already excellent mechanical properties of spider’s silk, producing nanocomposite fibers where the matrix of spider silk is reinforced with C60 molecules. These are deposited by Supersonic Molecular Beam Epitaxy (SuMBE) and are able to efficiently interact with silk, as evidenced by XPS analysis. As a consequence, upon proper adjustment of the fullerene kinetic energy the treated fibers show improved strength, Young modulus and toughness.